The Role Of Digital Marketing And Ambidexterity Integrated Solution In Improving MSME Business Performance - Endang Sulistiyani; Azizah Azizah; Isnaini Nurkhayati; Mohd Shamsuri Md Saad (Cita konsultindo, 2023)
The purpose of this study was to analyze several antecedent variables that influence MSME business performance and to determine the role of ambidexterity solutions in mediating the relationship between knowledge sharing and business performance. The population of this study is the owners of craft SMEs in Central Java. Samples were taken using purposive sampling method. Data were collected through questionnaires, and processed using Structural Equation Modeling analysis. Based on the results of the analysis, the five hypotheses that have been proposed show a significant positive effect. digital marketing and Ambidexterity integrated solutions are proven to play a role in mediating the relationship between knowledge sharing and business performance. The dominant influence between variables is shown from the relationship between knowledge sharing and digital marketing.